Modern weapons and military equipment for issue 4-2015 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
- Gear of the anti-terrorist groups of the unit for special purposes - Grenade Launchers ML40mk1 and ML40 mk2